Assessment of field performance and bruchid resistance during seed storage of a genetically modified cowpea expressing the alpha-amylase inhibitor 1 protein from common bean - Nboyine, Jerry A.; Umar, Muhammad L.; Adazebra, Gloria A.; Utono, Iliyasu M.; Agrengsore, Philip; Awuku, Frederick J.; Ishiyaku, Mohammed F.; Barrero, Jose M.; Higgins, Thomas J. V.; MacKenzie, Donald J. (Frontiers in Plant Science, 2024)
The cowpea weevil, Callosobruchus maculatus Fab., is the most economically important storage pest of cowpeas, causing up to 100 percent grain losses within six months of storage. To sustainably resist weevil damage, the cowpea cultivar IT86D-1010 was genetically modified via Agrobacterium-mediated transformation to produce event CSI-32, which expresses the kidney bean alpha-amylase inhibitor 1 (αAI-1) protein exclusively in the seed, providing suppression of weevil development. Trials were conducted in Ghana and Nigeria during the 2023 growing season to assess the performance in the field and in post-harvest storage of this transgenic event (CSI-32) and of four check lines: the non-transformed parental line (IT86D-1010) and three released varieties (SAMPEA 7, SAMPEA 20-T and IT13K-1070-2). Data collected from the field trials comprised plant growth parameters, pest infestations and damage, and grain yield. Harvested grain from each replicated entry was used in a storage assessment of bruchid resistance following artificial infestation with laboratory-reared cowpea weevils. Data were collected on egg oviposition, adult emergence, and grain damage as well as computation of median development period and Dobie’s susceptibility index for each entry. The agronomic performance and phenotypic characteristics of event CSI-32 were very similar to its parental counterpart and the other compared varieties. However, event CSI-32 exhibited complete suppression of weevil emergence and resistance to seed damage over the four-month period of the post-harvest study. This work represents the first field study of genetically modified cowpea expressing the αAI-1 protein. It demonstrates how a biotechnology solution to mitigate significant economic losses during cowpea storage, offers great potential for cowpea improvement programs.